Ophthalmic Single and Mixed Polymeric Nanomicelles using Brimonidine as a model drug: Preparation, Characterization, and Physical Properties Evaluation - Noor N. Alwiswasi; Al-Gawahri, Fatima (Iraqi Journal of Pharmaceutical Sciences, 2025)
Nanomicelles, a nanocarrier drug system, recently applied in medical research as a technique to deliver therapies to the targeted site. Normal nanomicelles building units are amphiphilic molecules (surfactants or polymers) containing hydrophobic tails and hydrophilic heads that self-assembled into the hydrophobic core-hydrophilic shell-like structure that dispersed into the aqueous media upon hydration. Polymeric nanomicelles had a lower critical micelle concentration by thousands of folds than surfactants of low molecular weight, resulting in a higher stability and circulation time after administration. Mixed nanomicelles have an extra advantage by improving the stability and encapsulation efficiency compared to single ones. Soluplus, an amphiphilic grafted copolymer used to enhance the solubility of the hydrophobic drug, and tocophersolan, a biocompatible and biodegradable vitamin E derivative polymer used as a stabilizer and permeability enhancer, were studied; both of them had hydrophobic and hydrophilic chains that are self-assembled into normal nanomicelles upon contact with aqueous media. This study aimed to prepare single soluplus and mixed soluplus-tocophersolan polymeric nanomicelles and compare their physical properties using a hydrophobic drug (brimonidine) as a model. The results showed that soluplus increases brimonidine solubility proportionally as its concentration increases. Soluplus concentration of 59mg/ml had the highest molar solubilization capacity (3.715) and the fraction of brimonidine encapsulated (0.872) with a negative value for Gibbes standard-free (-3.453), indicating a spontaneous nanomicelles formation. The physical appearance and the percentage of entrapment efficiency of the single soluplus nanomicelles were significantly affected by brimonidine concentration, while the particle size and the polydispersity index were not affected. The best single soluplus-brimonidine-loaded nanomicelles were transparent with particle size (75.75±1.13nm), polydispersity index (0.1243±0.02), and percentage of entrapment efficiency (53.49±0.58), was selected to prepare the mixed one. Variables including tocophersolan concentrations, the temperature of the hydration phase, and the tocophersolan addition phase, were studied regarding their effects on the physical properties of the mixed polymeric nanomicelles in which all of them affect highly significantly the particle size and the percentage of entrapment efficiency but, with no effect on the physical appearance and polydispersity index. The best mixed polymeric brimonidine-loaded nanomicelles were transparent, with tocophersolan added in the organic phase, and had a particle size of (79.55±0.24nm), polydispersity index (0.1222±0.00) and percentage of entrapment efficiency (62.18±0.23), with lowercritical micelle concentration of (3.467*10-7M). The mixed polymeric nanomicelle was more stable than the single one after storage at (4.0±2.0°C) for 90 days and had a faster in vitro release profile and a higher percentage of drug accumulated amount of (78.4±0.28%) within 15 minutes. The FTIR spectra for the individual components and the best-selected mixed nanomicelles indicated their compatibility, while the FESEM results showed a spherical morphology for the mixed polymeric nanomicelles with particle sizes close to that detected by Malvern Zetasizer. In conclusion, soluplus and tocophersolan could be used successfully to prepare spherical and transparent mixed polymeric nanomicelles incorporating a hydrophobic drug in their core with the desired physical properties with higher in vitro release amount and stability compared to single nanomicelles.